2005
DOI: 10.1038/sj.jp.7211333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Transcutaneous Jaundice Meter Following Hospital Discharge in Term and Near-Term Neonates

Abstract: OBJECTIVES:To evaluate performance of the Minolta JM-103 Jaundice Meter (JM) as a predictor of total serum bilirubin (TSB) in outpatient neonates during the first week postnatal, and to estimate the number of TSB determinations that might be avoided in clinical use. STUDY DESIGN:In neonates evaluated posthospital discharge, JM and TSB results were compared using linear regression and a Bland-Altman plot, and predictive indices were calculated for various JM cutoff values. Utilizing the 2004 American Academy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 21 publications
(33 reference statements)
7
55
6
Order By: Relevance
“…Overall, our results are similar to those of a large study evaluating the JM-103 in neonates X35 weeks, 3 and similar to or better than our experience using the JM-103 in larger, more mature neonates. 2 We found excellent precision between TcB results obtained by two independent observers. Means and s.d.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Overall, our results are similar to those of a large study evaluating the JM-103 in neonates X35 weeks, 3 and similar to or better than our experience using the JM-103 in larger, more mature neonates. 2 We found excellent precision between TcB results obtained by two independent observers. Means and s.d.…”
Section: Discussionmentioning
confidence: 61%
“…As in an earlier study using the JM-103 in our institution, there was a tendency for the TcB result to underestimate the corresponding TSB value. 2 In the current study, particularly in Groups 1 and 2, the regression lines drawn through individual group Bland-Altman data points indicated a tendency for the underestimation to be less at higher bilirubin values. In light of this trend, the clinician may be reassured as therapeutic intervention is, of course, more likely to be initiated at higher TSB values.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…29 Infants below standard TcB or TSB cut-offs may still develop hyperbilirubinemia, so even infants who have low pre-discharge screening levels should receive postnatal follow-up. 31 Studies have shown that the use of TcB and TSB in outpatient settings are also reliable 32,33 and can reduce readmissions for phototherapy. 34 The results of this study could be used by hospital postnatal discharge programs to ensure the most at-risk infants receive adequate information or screening before discharge and follow-up at home.…”
Section: Figurementioning
confidence: 99%
“…Transcutaneous bilirubin was measured within 30 min of blood sampling using the Konica Minolta/Dräger AirShields JM-103t Jaundice Metert (JM). 14,16 A single reading over the sternum was recorded; one investigator (HAB) performed all U/TSB and JM measurements.…”
Section: Methodsmentioning
confidence: 99%